New Potent Membrane-Targeting Antibacterial Peptides from Viral Capsid Proteins - Dias, Susana A.; Freire, João M.; Pérez-Peinado, Clara; Domingues, Marco M.; Gaspar, Diana; Vale, Nuno; Gomes, Paula; Andreu, David; Henriques, Sónia T.; Castanho, Miguel A. R. B.; Veiga, Ana S. (Frontiers in Microbiology, 2017)
The increasing prevalence of multidrug-resistant bacteria urges the development of new antibacterial agents. With a broad spectrum activity, antimicrobial peptides have been considered potential antibacterial drug leads. Using bioinformatic tools we have previously shown that viral structural proteins are a rich source for new bioactive peptide sequences, namely antimicrobial and cell-penetrating peptides. Here, we test the efficacy and mechanism of action of the most promising peptides among those previously identified against both Gram-positive and Gram-negative bacteria. Two cell-penetrating peptides, vCPP 0769 and vCPP 2319, have high antibacterial activity against S. aureus, MRSA, E. coli and P. aeruginosa, being thus multifunctional. The antibacterial mechanism of action of the two most active viral protein-derived peptides, vAMP 059 and vCPP 2319, was studied in detail. Both peptides act on both Gram-positive S. aureus and Gram-negative P. aeruginosa, with bacterial cell death occurring within minutes. Also, these peptides cause bacterial membrane permeabilization and damage of the bacterial envelope of P. aeruginosa cells. Overall, the results show that structural viral proteins are an abundant source for membrane-active peptides sequences with strong antibacterial properties.